THE IMPROVEMENT OF SKILLS IN EXPRESSING HYPOTHESIS AND DRAWING CONCLUSION IN SOLUBILITY AND SOLUBILITY PRODUCT THROUGH ADVANCE ORGANIZER LEARNING MODEL - elsa sinaga; noor fadiawati; nina kadaritna (Universitas Lampung, 2012)
This research was conducted to describe effectiveness of advance organizer learning model in improving skill in expressing hypothesis and drawing conclusion. Subject in this research was Grade XI students in classroom IPA3 in State Senior High School 7 in Bandar Lampung in even semester of academic year 2011-2012. This research used pre-experiment method with One-group Pretest-posttest design. Effectiveness of advance organizer learning model was indicated by improvement of n-gain values of pretest and posttest. The n-gain estimation results were subsequently interpreted with n-gain index suggested by Hake. The research results showed that the averages of n-gain of skill in expressing hypothesis and drawing conclusion were 0.55 (middle category) and 0.47 (middle category) respectively. The conclusion is that the advance organizerlearning model is effective in improving skills of expressing hypothesis and drawing conclusion.Keywords: advance organizer learning model, skills in expressing hypothesis and drawing conclusion